Synchronous Primary Adenocarcinoma of Distal Common Bile Duct and Gall bladder - Bohara, Tanka Prasad; Paudyal, Sanjaya; Chaudhary, Prakash; Joshi, Mukund Raj (Journal of Nepal Health Research Council, 2022)
Synchronous primary cancer of the gall bladder and distal common bile duct is rare. There are only few case reports and case series available of these synchronous cancers. Management of this tumor is individualized in these case reports and series based upon the presentation. We present a case of a patient who had multifocal adenocarcinoma involving distal common bile duct and gall bladder. Keywords: Distal common bile duct cancer; gall bladder cancer; synchronous primary